Dementia and psychotropic medications are associated with significantly higher mortality in geriatric patients hospitalized with COVID-19: data from the StockholmGeroCovid project - Secnik, Juraj; Eriksdotter, Maria; Xu, Hong; Annetorp, Martin; SweGeroCOVID Project; Rytarowski, Aleksander; Johnell, Kristina; Hägg, Sara; Religa, Dorota (Alzheimer's research & therapy, 2023)
BACKGROUND: Dementia and psychotropic medications are discussed as risk factors for severe/lethal outcome of the coronavirus disease 2019 (COVID-19). We aimed to explore the associations between the presence of dementia and medication use with mortality in the hospitalized and discharged patients who suffered from COVID-19. METHODS: We conducted an open-cohort observational study based on electronic patient records from nine geriatric care clinics in the larger Stockholm area, Sweden, between February 28, 2020, and November 22, 2021. In total, we identified 5122 hospitalized patients diagnosed with COVID-19, out of which 762 (14.9%) patients had concurrent dementia and 4360 (85.1%) were dementia-free. Patients' age, sex, baseline oxygen saturation, comorbidities, and medication prescription (cardiovascular and psychotropic medication) were registered at admission. The hazard ratios (HRs) with 95% confidence intervals (CIs) of in-hospital, 30-day, 90-day, 365-day post-discharge, and overall mortality during the follow-up were obtained. Then, the associations of dementia and medication use with mortality were determined using proportional hazards regression with time since entry as a time scale. RESULTS: After adjustment, dementia was independently associated with 68% higher in-hospital mortality among COVID-19 patients compared to patients who were dementia-free at admission [HRs (95% CI) 1.68 (1.37-2.06)]. The increase was consistent post-discharge, and the overall mortality of dementia patients was increased by 59% [1.59 (1.40-1.81)]. In addition, the prescription of antipsychotic medication at hospital admission was associated with a 70% higher total mortality risk [1.70 (1.47-1.97)]. CONCLUSIONS: The clinical co-occurence of dementia and COVID-19 increases the short- and long-term risk of death, and the antipsychotics seem to further the risk increase. Our results may help identify high-risk patients in need of more specialized care when infected with COVID-19.
Keywords: Dementia; Psychotropic Drugs; psychotropní léky; Aged; COVID-19; Antipsychotic Agents; propuštění pacienta; antipsychotika; Humans; senioři; lidé; Aftercare; Patient Discharge; Antipsychotics; následná péče; Mortality